2012
DOI: 10.1007/s12665-012-1835-4
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic impacts on reduced inorganic sulfur and heavy metals in coastal surface sediments, north Yellow Sea

Abstract: This study investigated the organic carbon, reduced inorganic sulfur, and heavy metal distribution in superficial sediments at an estuary, a wastewater discharge area, and a mariculture area, as compared with an unpolluted distal site, in the north Yellow Sea, China. Sediment grain size, acid volatile sulfur (AVS), chromium (II)-reducible sulfur, elemental sulfur, total sulfur, total organic carbon (TOC), total nitrogen and trace metal content were determined for each site. These results indicate that pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
(38 reference statements)
2
6
0
Order By: Relevance
“…In the marine area, AVS concentrations fall in a wide range from 1.17 to 371 lg g -1 (Table 2). The higher end of this range is consistent with AVS concentrations found in northern Yellow Sea coastal surface sediments (202-344 lg g -1 ) (Sheng et al 2013a), but 89 % (24 of 27) of our samples fall below the lower end of their range, consistent with the high TOC/TS ratios found in these sediments (Table 3). In the rivers, the AVS levels (6.56-6,832 lg g -1 ) are consistent with many natural estuaries (e.g., 2,880 lg g -1 , Morse and Cornwell 1987) and Shijing River (1,043 lg g -1 ) located in the Pearl River delta (Sheng et al 2011).…”
Section: Distribution Of Avs Crs and Es In Sedimentsupporting
confidence: 89%
See 1 more Smart Citation
“…In the marine area, AVS concentrations fall in a wide range from 1.17 to 371 lg g -1 (Table 2). The higher end of this range is consistent with AVS concentrations found in northern Yellow Sea coastal surface sediments (202-344 lg g -1 ) (Sheng et al 2013a), but 89 % (24 of 27) of our samples fall below the lower end of their range, consistent with the high TOC/TS ratios found in these sediments (Table 3). In the rivers, the AVS levels (6.56-6,832 lg g -1 ) are consistent with many natural estuaries (e.g., 2,880 lg g -1 , Morse and Cornwell 1987) and Shijing River (1,043 lg g -1 ) located in the Pearl River delta (Sheng et al 2011).…”
Section: Distribution Of Avs Crs and Es In Sedimentsupporting
confidence: 89%
“…Berner (1982) indicated that the C/S mass ratio in normal marine sediments (deposited under an oxic water column) was between 0.75 and 1.35 (calculated from molar ratio 2.0-3.6). Research into the distribution and transformations of reduced inorganic sulfur (RIS) in freshwater, estuary, peatland, salt marsh, and marine sediments (Berner 1984;Coulson et al 2005;Bottrell et al 2010;Sheng et al 2011Sheng et al , 2013aMortimer et al 2011) has shown that pyrite and ferrous monosulfide are the two major end products in sediments, where dissimilatory sulfate reduction is active (Zhu et al 2014). Although sulfate and Fe(III) reduction along with the microbially mediated formation of sulfide minerals can increase alkalinity and reduce metal availability (Burton et al 2005;Mortimer et al 2011), oxidation of sedimentary sulfide during sediment resuspension may cause rapid deoxygenation and acidification of overlying water, posing an environmental hazard (Morse and Rickard 2004;Sullivan et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The average water depth is less than 15 m. The quality of the marine environment is not only affected by mariculture, but also by industrial, agricultural, and domestic sewage discharges by local Zhifu and Laishan districts. Studies showed that a large quantity of industrial materials and wastewater are discharged by the Zhifu Island sewage treatment plant every year (Sheng et al, 2012). In this experiment, all sampling stations were located in Sishili Bay within the area from 37 • 26 49.44 N to 37 • 38 10.14 N and 121 • 24 0.00 E to 121 • 40 27.85 E. The details can be found in Supplementary Table S1.…”
Section: Sampling Stationsmentioning
confidence: 99%
“…Sediments play an important role in the evolution of the aquatic environment, as many contaminants from municipal, industrial and non-point sources are associated with solid particles that accumulate as sediments, creating a potential threat to benthic organisms (Dittrich et al, 2013;Sheng et al, 2013). Sediments can also be re-suspended at high flow rates or within estuarine turbidity maxima and pollutants can be released back into the water column, causing deterioration of water quality (Liao et al, 2015;Seitzinger et al, 2010;Widerlund and Davison, 2007).…”
Section: Introductionmentioning
confidence: 99%